60.7k views
0 votes
X=r-h/y solve for h and then for r

User Elli White
by
5.7k points

2 Answers

5 votes
x=(r-h)/y
xy=r-h
xy-r=-h
r-xy=h

x=(r-h)/y
xy=r-h
xy+h=r
User MEMark
by
5.8k points
2 votes

Answer:


r=x+(h)/(y)

Explanation:

X=r-h/y


x=r-(h)/(y)

Solve the equation for 'r'

To solve the equation for 'r', we add the fraction on both sides.


x+(h)/(y)=r-(h)/(y)+(h)/(y)

So right side we are left with 'r'


r=x+(h)/(y)

We got the 'r' alone. So we solve for 'r'

User Weltraumpirat
by
5.2k points